STYLISTICS FEUTURES OF SPORT TERMS IN ENGLISH AND UZBEK LANGUAGE - Niyazova, Sevara Azamat qizi; Sarimsoqov, X (INTERNATIONAL CONFERENCES, 2023)
This article deals with borrowing vocabulary in the field of sports from English to Uzbek. It is established that in the Uzbek sports terminology there is a large number of anglicisms, which is explained by the development of appropriate technology for various sports in the English-speaking world. In the course of the study, a lexico - semantic analysis of Uzbek sports terms of English origin is carried out, and also the peculiarities of their word formation are revealed. The aim of this paper looks at the metaphors and idioms in the English language that have sports as their motivation and attempts to draw certain parallels with their corresponding semantic equivalents in Serbian. In the methodology part, the paper looks at more than 20 different metaphorical sport expressions, while the introduction, results, discussion and conclusion explore the theoretical bases that underpin any twist in meaning once a group of several words are joined together, thereby changing the sum of their individual meanings.